1991
DOI: 10.1007/bf01972510
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of RU29246 (HR916 metabolite) compared with four other oral beta-lactams tested against more than 5000 clinical isolates

Abstract: The activity of RU29246, the active metabolite of the oral cephalosporin ester HR916, was compared in a multicenter study with that of the four oral beta-lactam antibiotics cephalexin, cefaclor, cefixime and amoxicillin/clavulanate (amoxicillin/CA). RU29246 was generally 2- to 8-fold more active than the other oral cephalosporins and comparable to amoxicillin/CA against staphylococci, and was the most active cephalosporin against group B streptococci. All four cephalosporins were ineffective against enterococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Staphylococcus aureus strains were susceptible to cephalexin in-vitro 41 and this findings is in agreement with the result of this study. Also all strains of Staphylococcus aureus were found to be susceptible (sensitive and moderately sensitive) to cephalexin and cephradine at concentrations ranging between 3.125 µg/m -50 µg/ml.…”
Section: Resultssupporting
confidence: 93%
“…Staphylococcus aureus strains were susceptible to cephalexin in-vitro 41 and this findings is in agreement with the result of this study. Also all strains of Staphylococcus aureus were found to be susceptible (sensitive and moderately sensitive) to cephalexin and cephradine at concentrations ranging between 3.125 µg/m -50 µg/ml.…”
Section: Resultssupporting
confidence: 93%
“…Like all beta-lactam antibiotics, cefixime ability to interfere with PBP-mediated cell wall synthesis ultimately leads to cell lysis. (19) In this research a study of the effect of phenolic compounds extracted from green tea interpenetrating with drug cefixime against the bacteria Pseudomonas aeruginosa, Escherichia coli gives an idea of the overlap between each of them as the results showed that the drug cefixime gives high inhibitory effect in the bacterial species under study these results were in agreement with other studies (20,21) which mentioned that the drug cefixime has a strong activity against gramnegative bacteria like Pseudomonas aeruginosa, Escherichia coli while this result disagreement with (3,22,23) which find that the cefixime is inactive against Pseudomonas aeruginosa. before adding the phenolic extracts which was different influence in these types of bacteria but was less effective than drug cefixime which inhibits the growth of bacteria in lowest concentration This drug may be exert its effect by interfering with the structural cross linking of peptidoglycans in bacterial cell walls.…”
Section: Resultssupporting
confidence: 81%
“…This stability is responsible for the ex cellent in vitro activity of this compound against many gram-negative and gram-posi tive bacteria. Jones et al [5,6] were also resistant to imipenem. On the other hand, only 5 isolates of E. cloacae were resist ant to this cephem as compared with 9 for imi penem.…”
Section: Discussionmentioning
confidence: 99%